Digitalization as a driver for smart economy in the post-COVID-19 era - Reis, Leonilde, 1962-; Carvalho, Luísa Cagica, 1970-; Silveira, Clara, 1964-; Xara-Brasil, Duarte, 1970- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book presents a global and multidisciplinary approach that can contribute to a better understanding of the relationship and mutual influence of digital, entrepreneurship, marketing, sustainability, customer relationship management and innovation scientific areas"--